Legal adaptation of the pledge to transfer ownership of real estate in Iraqi law - Hussain, Farhad Hatem (The Scientific Journal of Cihan University– Sulaimaniya, 2021)
it is known that rights in rem in property were and still are of great importance in the areas of legal relations among the rest of the other rights, given the human need in real estate ownership and the large number of transactions in it. This has prompted the Iraqi legislator to provide it with a set of guarantees and incorporates them in the public order, and that it is not permissible to agree on what opposes its rules, and the formal element has been granted to it. However, the Iraqi legislator’s remedy of the issue of the commitment to transfer ownership of the real estate or rights in rem right and the subsequent legal effects have not met the required level that guarantees the rights of the parties, especially the contractor or in his interest, and the legislator has failed The provisions of the undertaking only to undertake to transfer the ownership of the real estate and the right to dispose of it, without including other rights in rem in property. For this reason we have tried to answer the questions that we raised regarding the treatment of this subject, and it is noticeable in the text of Article 1127 of the Iraqi Civil Code that it only included obligating the obligor to pay compensation when the obligor breaches the implementation of the commitment to transfer the ownership of the property to the other party, or to oblige the contractor when breaching the obligation to pay the consideration regardless of whether the compensation is stipulated in the contract or not. Nonetheless after the Revolutionary Command Council issued Decision No. 1198 of 1977 amended by Resolution 1428 of 1984, this commitment resulted in two important legal effects, namely determination of the compensation that results from the breach of the pledge to transfer the ownership of the property on First, the condition that; it is not less than the difference between The two alternatives (the real estate sale allowance for the date of purchase and sale, and the alternative on the date of the transfer), and the second of is the possibility of requesting real implementation when the ownership conditions mentioned in the decision are fulfilled